Analysis of Demographic Characteristics of Elderly Hypertension Patients at Sananwetan Primary Health Centerimary Health Center - Yudhawati, Sherlyana Kartika; Mujito, Mujito; Hariyanto, Tanto (Health Gate, 2025)
Aging leads to physiological changes such as decreased vascular elasticity and impaired blood pressure regulation, increasing the risk of hypertension. Demographic factors such as age, sex, education level, and socioeconomic status also contribute. This study aimed to analyze the relationship between demographic characteristics and the prevalence of hypertension among older adults at Sananwetan Primary Health Center. A quantitative descriptive design was employed, with purposive sampling of 100 elderly individuals diagnosed with hypertension. Primary data were collected through interviews using a modified WHO STEPS questionnaire, and secondary data were obtained from health records. Data were analyzed using descriptive and inferential statistics (Chi-Square test). Most respondents were aged 60–74 years (77%), female (68%), had a high school education (50%), and belonged to the middle socioeconomic group (85%). The Chi-Square test showed significant associations between age (p = 0.019), sex (p = 0.007), education level (p = 0.034), and socioeconomic status (p = 0.016) with the prevalence of hypertension. In conclusion, demographic factors influence the risk of hypertension in older adults. Health education-based interventions, improved access to services, and promotion of healthy lifestyles are essential strategies to reduce hypertension prevalence in high-risk elderly populations.